AMBIGUITAS DAN DAMPAK NEGATIF PEMILIHAN KEPALA DAERAH LANGSUNG DALAM PERSPEKTIF FILOSOFI PANCASILA - Ridhuan, Syamsu; Ningsih, Rahmah; Nur, Syurya Muhammad (Eduscience : Jurnal Ilmu Pendidikan, 2021)
There is no relevance of the direct regional head election system to democracy in the perspective of the Pancasila philosophy. This is the conclusion of the study, measuring the level of relevance of the direct election system for regional heads with democracy in the perspective of the Pancasila philosophy. A reflection of Pancasila education learning in universities. The study analyzed as many as 763 students as respondents who were taking Pancasila Education courses. Analysis of the research ambiguity occurs, the implementation of the regional head election directly received the support of the wider community. However, the philosophy of Pancasila is not inherent in the existence of the essence of the values and norms of Pancasila, the fourth principle of Pancasila "Democracy Led by WisdomÂ  in Representative Deliberations" is philosophically relevant to indirect regional head elections (representative democracy). The negative impact can damage the nation's morale, because money politics often occurs during campaigns, the intention to return capital instantly, so that regional heads are prone to being entangled in corruption, and acts of anarchy often occur as a reaction to disappointment and dissatisfaction. It is recommended that if the democracy of direct regional head elections is still carried out, it is necessary to educate the public's political intelligence and strict law enforcement to handle cases of violations.Â Keywords: Pilkadasung, democracy, Pancasila philosophy